Strategi Promosi Wedding Organizer Di Bengkulu Melalui Instagram - Putri, Yuni Herlina; Yanto, Yanto; Sari, Sapta (Universitas Dehasen Bengkulu, 2025)
Promotions can also help build brand image, communicate product advantages, and create customer loyalty. With the right promotional strategy, companies can reach target audiences effectively and improve market position. The purpose of this research is to find out promotional strategies for wedding organizers through the History Wedding Planner Instagram account. This type of research uses a qualitative descriptive approach. The theory used in this research is Integrated Marketing Communication (IMC). The conclusion of this research can be seen from the promotional strategy implemented by History Wedding Planner involving the use of advertising via Reels, giving discounts, and limiting the number of people in certain promotions. History Wedding Planner also builds good relationships with traditional stakeholders to strengthen a positive image in society. Although not currently using influencers, History Wedding Planner relies on an internal team in creating promotional videos and plans to involve influencers in the future. Apart from that, History Wedding Planner also implements direct marketing by distributing business cards to create personal interactions with customers, which is effective in strengthening the brand and attracting potential customers. cards to create personal interactions with customers, which is effective in strengthening the brand and attracting potential customers..